2015
DOI: 10.1038/ncomms8837
|View full text |Cite
|
Sign up to set email alerts
|

Geologic controls on supercritical geothermal resources above magmatic intrusions

Abstract: A new and economically attractive type of geothermal resource was recently discovered in the Krafla volcanic system, Iceland, consisting of supercritical water at 450 °C immediately above a 2-km deep magma body. Although utilizing such supercritical resources could multiply power production from geothermal wells, the abundance, location and size of similar resources are undefined. Here we present the first numerical simulations of supercritical geothermal resource formation, showing that they are an integral p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
98
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 125 publications
(99 citation statements)
references
References 32 publications
1
98
0
Order By: Relevance
“…The simulations describe the development of a saline geothermal system within a two‐dimensional vertical section above a magmatic body intruded into host rocks with a permeability of 10 −15 m 2 initially containing pore waters with seawater salinity. We choose this permeability value because previous studies have shown that it is common in natural systems [ Björnsson and Bödvarsson , ; Manning and Ingebritsen , ] and close to optimal for the formation of spatially extensive supercritical geothermal resources in pure water systems [ Scott et al ., , ]. We performed simulations testing possible conditions for the Reykjanes system, in which intrusion depth and brittle‐ductile transition temperature are treated as variables.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The simulations describe the development of a saline geothermal system within a two‐dimensional vertical section above a magmatic body intruded into host rocks with a permeability of 10 −15 m 2 initially containing pore waters with seawater salinity. We choose this permeability value because previous studies have shown that it is common in natural systems [ Björnsson and Bödvarsson , ; Manning and Ingebritsen , ] and close to optimal for the formation of spatially extensive supercritical geothermal resources in pure water systems [ Scott et al ., , ]. We performed simulations testing possible conditions for the Reykjanes system, in which intrusion depth and brittle‐ductile transition temperature are treated as variables.…”
Section: Methodsmentioning
confidence: 99%
“…In systems with meteoric‐derived, dilute water, liquid‐vapor phase separation is limited to pressures and temperatures below the critical point of water (22.055 MPa/373.976°C) [ Haar et al ., ]. At higher temperatures and pressures, such systems may develop economically interesting, supercritical geothermal resources above the magma [ Scott et al ., ], which were encountered in the Iceland Deep Drilling Project (IDDP) well 1 at the Krafla volcano [ Elders et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…As shown from fluid flow modeling studies (e.g. Scott et al, 2015), boiling zones can be expected to be present in higher temperature geothermal systems, leading to a further decrease of the seismic velocities. The effect of the water-steam transition on seismic velocities was examined by Ito et al (1979) for a water-filled sandstone.…”
Section: Velocity Anomalies Of Geothermal Resources Versus Backgroundmentioning
confidence: 98%
“…Recently, efforts have been made to investigate how to exploit economically attractive fluids in supercritical conditions ( T>374 °C and P>21 MPa for pure water) (Croucher & O'Sullivan, ; Reinsch et al, ; Scott et al, ). Supercritical fluids have high rates of mass transport due to the highly enhanced ratios of buoyancy forces to viscous forces (Dunn & Hardee, ).…”
Section: Introductionmentioning
confidence: 99%